The effects of different inotropic agents on respiratory conditions in hospitalized COVID-19 patients: A Retrospective study - Abdulsalam Mohammed Aleid; Mohammed Yousef Alessa; Loai Saleh Albinsaad; Saud Nayef Salem Aldanyowi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: The use of inotropic agents is common in hospitalized patients with COVID-19 to support cardiovascular function and oxygen delivery. However, the effects of different inotropic agents on respiratory status and outcomes in COVID-19 patients are not well established. This retrospective study aimed to compare the impact of commonly used inotropic vasopressors (vasopressin, norepinephrine, epinephrine, dopamine) and inotropes (dobutamine) on respiratory parameters and outcomes in COVID-19 patients requiring intensive care. Methods: This was a retrospective study conducted at 26 hospitals in Saudi Arabia. Medical records of 1,491 adult COVID-19 patients admitted to the intensive care unit (ICU) between September 2020 to December 2020 were reviewed. Data collected included demographic characteristics, comorbidities, arterial blood gas measurements, duration of mechanical ventilation, ICU and hospital length of stay, and in-hospital mortality. The primary exposure was the type and dose of inotropic agents administered. The primary outcomes were duration of mechanical ventilation, ICU and hospital length of stay. Secondary outcomes included arterial blood gas measurements and in-hospital mortality. Statistical analysis was performed using chi-square tests and ANOVA. Results: A total of 1,491 patients were included, with a mean age of 55.9 years and 73.7% were males. The most commonly used inotropic agents were norepinephrine (60.4% of patients), dobutamine (43.3%), dopamine (32.6%), epinephrine (18.8%) and vasopressin (2.7%). Patients receiving vasopressin had significantly higher Pao2/Fio2 ratios (p=0.012), shorter duration of mechanical ventilation (p=0.021) and ICU length of stay (p=0.038). Those receiving norepinephrine had worse Pao2/Fio2 ratios (p=0.001), longer duration of mechanical ventilation (p=0.002), ICU (p=0.003) and hospital length of stay (p=0.012). Dobutamine was associated with lower in-hospital mortality (p=0.049). Epinephrine and dopamine did not have a significant impact on any outcomes. Conclusion: Among COVID-19 patients requiring ICU admission, the use of vasopressin was associated with better respiratory function and shorter durations of ventilation and ICU stay compared to other inotropic agents. In contrast, norepinephrine use was linked to worse oxygenation and longer treatment courses. Dobutamine may reduce mortality. These results suggest vasopressin may be preferable to norepinephrine for hemodynamic support in critically ill COVID-19 patients. However, the retrospective study design limits causal inferences. Further prospective studies are needed to establish optimal inotropic strategies in this population.